(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The Sentence solves one of the numerous appeals of unconstitutionality presented in front of the RD-ley 16/2012, endorsing the exclusion of foreigners in an irregular situation of free access to the health care system. Justification of the measure is one of the keys of the argumentation. In this case, the limitation of a social right (access to health care) lies on considerations related to budgetary stability and sustainability of public services. In this scenario, the issue of efficiency and effectiveness becomes relevant, in close connection with the principle of proportionality.